Efficacy and safety of erenumab (AMG334) in chronic migraine patients with prior preventive treatment failure: A subgroup analysis of a randomized, double-blind, placebo-controlled study - Ashina, Messoud; Tepper, Stewart; Brandes, Jan Lewis; Reuter, Uwe; Boudreau, Guy; Dolezil, David; Cheng, Sunfa; Zhang, Feng; Lenz, Robert; Klatt, Jan; Mikol, Daniel D (Cephalalgia, 2018)
Background Erenumab was effective and well tolerated in a pivotal clinical trial of chronic migraine. Here, we evaluated efficacy and safety of monthly erenumab (70 mg or 140 mg) versus placebo in the subgroup of patients who had previously failed preventive treatment(s) (≥ 1, ≥ 2 prior failed medication categories) and in patients who had never failed. Methods Subgroup analyses evaluated change from baseline in monthly migraine days; achievement of ≥ 50% and ≥ 75% reduction in monthly migraine days; and change in monthly acute migraine-specific medication days. Adverse events were evaluated for each subgroup. Results Treatment with both doses of erenumab resulted in greater reductions in monthly migraine days (primary endpoint) at Month 3 (treatment difference [95% CI], never failed subgroup: -2.2 [-4.1, -0.3] for 70 mg and -0.5 [-2.4, 1.5] for 140 mg; ≥ 1 prior failed medication categories subgroup: -2.5 [-3.8, -1.2], for 70 mg and -3.3 [-4.6, -2.1] for 140 mg; ≥ 2 prior failed medication categories subgroup: -2.7 [-4.2, -1.2], for 70 mg and -4.3 [-5.8, -2.8] for 140 mg). Similar results were observed in the monthly acute migraine-specific medication days endpoint, and in the achievement of ≥ 50% and ≥ 75% reduction in monthly migraine days. There were no new or unexpected safety issues. Conclusion Erenumab showed consistent efficacy in chronic migraine patients who had failed prior preventive treatments and was well tolerated across subgroups.
Keywords: peptid spojený s genem pro kalcitonin; monoklonální protilátky; Antibodies, Monoclonal; Adult; dvojitá slepá metoda; Male; Double-Blind Method; prior preventive treatment failure; lidé; lidé středního věku; Humans; clinical trial of prophylactic migraine treatment; prior prophylactic treatment failure; Middle Aged; Migraine Disorders; Antibodies, Monoclonal, Humanized; Erenumab; mužské pohlaví; humanizované monoklonální protilátky; migréna; dospělí; Calcitonin Gene-Related Peptide; ženské pohlaví; chronic migraine; Female